A RESPONSABILIDADE CIVIL DAS EMPRESAS GIGANTES DA INTERNET: ASPECTOS DE DIREITO INTERNACIONAL PRIVADO, PELO PRISMA DO DIREITO FRANCÊS E DO DIREITO DA UNIÃO EUROPEIA - Boskovic, Olivera (Law, State and Telecommunications Review, 2020)
Objective ”“ The article offers an original contribution to the debate about the application of substantive law and the eligible jurisdiction that should judge the liabilities disputes between the so-called Internet giants' enterprises and the users. Methodology/approach/design ”“ The article brings a bibliographical and case law review of both France and the European Union about International Private Law applicable to the liability violations made by the so-called Internet giants' enterprises. Findings ”“ The article shows a legal theory central problem, which is the best way to define both the substantive law and the jurisdiction that should judge transfrontier liabilities in legal cases. The best solution would be to apply the so-called focus theory, i.e. the application of the substantive law and the jurisdiction following the local where the damage happens. Notwithstanding, this general application of the focus theory could impose limits on the future substantive reparation that the courts may grant to the victims. Besides, such general application collides with the traditional forum selection clauses that the giant Internet firms usually use to demand that the judgment of liability lawsuits solely by the United States courts. Practical implications ”“ The article is an important introduction to the choice of substantive law and jurisdiction applicable to the liability lawsuits filed against the giant Internet enterprises. This debate has a clear practical application that will become more important as the European Union General Data Protection Regulation (GDPR) enters in force and prescribes its transfrontier application. Originality/value ”“ The article enlightens a very important legal debate about the European Union Law that has some regulations (Rome I, Rome II, and Brussels I) to prescribe what substantive law and which jurisdiction may be of use to judge civil liability violations. This legal debate will grow in importance since the GDPR will give motives to a whole lot of new lawsuits about data protection.